A STUDY OF INTENTION TO REDUCE INDONESIA'S FOOD WASTE - Teresia Debby; Atik Aprianingsih; Agus Hasan Pura Anggawidjaja; Wisnu Wardhono; Ivan Prasetya; Chris Petra Agung; Avadhut Patwardhan (Faculty of Economics and Business Udayana University, 2025)
Food waste has become a big problem in Indonesia. According to the data in May 2023, Indonesia was placed in the third sport in the rank of the world’s largest food waste producer in the world. Food waste makes up to 40.98% of the total waste, this data is taken from the Ministry of Environment and Forestry in 2023. This phenomenon contradicts with the reality of many of its citizen are still struggling to find food to eat. Moral norms hold a high place in Indonesia, and this can be used as one driver to reduce the food waste. This study has goal to see how moral norms for food waste reduction and self-efficacy towards food waste reduction impact the intention to reduce food waste in Indonesia. This study uses technique, structural equation model-partial least squares (SEM-PLS). In total, there are 157 respondents who have participated in this study. The results clearly shown that there is a positive correlation between 2 variables (moral norms for food waste reduction and self-efficacy toward food waste) with food waste reduction intention. To close, Indonesia with its moral norms towards food waste has helped with the intention to reduce food waste. However, the intention alone is not enough. There must be a strong incentive to change the intention into real action.